Transcription factor EB overexpression prevents neurodegeneration in experimental synucleinopathies - Arotcarena, Marie-Laure (JCI Insight, 2019)
The synucleinopathies Parkinson’s disease (PD) and Multiple system atrophy (MSA) — characterized by α-synuclein intracytoplasmic inclusions into, respectively, neurons and oligodendrocytes — are associated with impairment of the autophagy-lysosomal pathways (ALP). Increased expression of the master regulator of ALP, transcription factor EB (TFEB), is hypothesized to promote the clearance of WT α-synuclein and survival of dopaminergic neurons. Here, we explore the efficacy of targeted TFEB overexpression either in neurons or oligodendrocytes to reduce the pathological burden of α-synuclein in a PD rat model and a MSA mouse model. While TFEB neuronal expression was sufficient to prevent neurodegeneration in the PD model, we show that only TFEB oligodendroglial overexpression leads to neuroprotective effects in the MSA model. These beneficial effects were associated with a decreased accumulation of α-synuclein into oligodendrocytes through recovery of the ALP machinery. Our study demonstrates that the cell type where α-synuclein aggregates dictates the target of TFEB overexpression in order to be protective, paving the way for adapted therapies.